2022
DOI: 10.1097/mpg.0000000000003643
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab Therapy in Pediatric Crohn Disease: A 2-Year Follow-Up Comparing “Top-Down” and “Step-Up” Strategies

Abstract: Objectives: European Crohn’s Colitis Organization (ECCO) and the European Society of Pediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) guidelines recommend the early use of anti-tumor necrosis factor (TNF) biologicals in pediatric Crohn disease (CD) patients with positive predictors for poor outcome. The objective of the present study was to compare early “Top-Down” use of adalimumab (ADA) immunomodulator/biologics-naive patients to conventional “Step-Up” management. Methods: One hundred and twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(48 reference statements)
2
3
0
Order By: Relevance
“…In addition, Jongsma and colleagues found that the probability of continued clinical remission at week 52 with monotherapy of azathioprine was higher in children who received infliximab as first-line therapy to induce remission [ 50 ]. Comparable results were shown for adalimumab [ 72 ]. In Crohn’s disease, early and effective use of TNF-α blockers also prevented the development of disease complications, for example, strictures or penetrating ulcerations and disease progression [ 28 ].…”
Section: Early and Effective Use Of Tnf-α Blockers Prevents Disease P...supporting
confidence: 55%
“…In addition, Jongsma and colleagues found that the probability of continued clinical remission at week 52 with monotherapy of azathioprine was higher in children who received infliximab as first-line therapy to induce remission [ 50 ]. Comparable results were shown for adalimumab [ 72 ]. In Crohn’s disease, early and effective use of TNF-α blockers also prevented the development of disease complications, for example, strictures or penetrating ulcerations and disease progression [ 28 ].…”
Section: Early and Effective Use Of Tnf-α Blockers Prevents Disease P...supporting
confidence: 55%
“…In addition, the probability of continued clinical remission at week 52 with azathioprine monotherapy was higher in children who received infliximab as a first-line remission-inducing therapy. Comparable results were shown for adalimumab [47].…”
Section: Tnf-α Inhibitor Therapy and Its Clinical Impactsupporting
confidence: 55%
“…Therapy with TNF-α inhibitors can thus be used to break the vicious cycle of chronic inflammation early and effectively [46,47], since TNF-α blockade weakens several inflammatory networks and promotes anti-inflammatory processes [13,14,[29][30][31][32]48]. Consequently, the blockade of TNF-α has a systemic effect and is not restricted to a specific inflammatory disease, which is why the development of further organic manifestations can be prevented and chronic comorbidities can be treated efficiently [6,10,11,[49][50][51].…”
Section: Tnf-α Inhibitor Therapy Restores Cytokine Balance and Normal...mentioning
confidence: 99%
“…Among patients without endoscopic recurrence, top-down reduced risk of these outcomes (clinical recurrence HR 0.59, p = 0.025; bowel damage progression HR 0.73, p < 0.001) [ 73 ]. Another study compared top-down vs. step-up ADA strategies in 120 pediatric patients over 24 months [ 113 ]. At the endline, remission was higher in the top-down group (73% vs. 51%, p < 0.01).…”
Section: Prophylaxis Of Postoperative Recurrencementioning
confidence: 99%
“…A propensity analysis found top-down to be more effective in maintaining remission (HR = 0.36, 95% CI 0.15–0.87, p = 0.02). Top-down mainly used monotherapy vs. combination in step-up ( p < 0.001) [ 113 ]. Previous results may be indirectly confirmed by a retrospective Scottish study, which found 5-year surgery risks fell from 20.4% to 13.0% ( p < 0.001), while biologic use rose from 5.7% to 44.9% ( p < 0.001) from 2000–2004 to 2014–2017 [ 114 ].…”
Section: Prophylaxis Of Postoperative Recurrencementioning
confidence: 99%